Montessori-Pädagogik und die Erziehungsprobleme der Gegenwart - Fuchs, Birgitta; Harth-Peter, Waltraud; Montessori, Maria (Königshausen u. Neumann, 1989)
Literaturangaben
Includes bibliographical references
Keywords: Konferenzschrift -- 1988 -- Würzburg; Montessori-Pädagogik